Analysis of the potential impact of car subscriptions on the german automotive market - Stuchlik, Maximilian (2021)
The automotive industry is currently subverting several trends. Its traditional focus on product and sales with ownership as the goal is changing to a customer-centric focus with the goal of providing access to car-based services. The car subscription is a fairly new form of these access-based services. The aim of this thesis is to analyse the potential influence of car subscriptions on car purchases, financing, and leasing in the private customer sector in Germany. Secondary data was collected by reviewing the current literature on access-based services, mobility behaviours and leading trends. The primary analysis consisted of a customer survey to gather perceptions of adults in Germany on car subscriptions. Furthermore, a scenario analysis after Schoemaker (1995) was conducted with insights from five expert interviews. The findings revealed that car subscriptions are still a niche topic and, in terms of market shares, are far behind the other financing forms. However, car subscriptions are seen as more interesting than leasing and financing. Thus, car subscriptions will become the fourth pillar of financing and, according to the trend scenario, may account for 20% of market shares in 2030, overtaking cash purchase and aligning with leasing. Overall, car subscriptions are here to stay.